Does the balance strategy during walking in elderly persons show an association with fall risk assessment?. (16th April 2020) - Ohtsu, Hajime; Yoshida, Shinya; Minamisawa, Tadayoshi; Katagiri, Natsuki; Yamaguchi, Tomofumi; Takahashi, Toshiaki; Yomogida, Shin-ichi; Kanzaki, Hideto
Abstract: The primary objective of this study was to clarify whether balance evaluation during walking in elderly people was related to fall risk assessment; the second objective was to clarify the difference in balance strategy between young and elderly people based on the balance evaluation through a gait cycle. Thirty healthy young adults and 25 healthy elderly adults participated. All participants performed walking at their preferred speed and at a fast speed. Based on the margin of stability (MoS), balance during a gait cycle was divided into medial/lateral and anterior/posterior direction (ML/AP-MoS). Positive/negative integral values of ML-MoS were defined as ML-MoSPOS /ML-MoSNEG, and the average of AP-MoS over the gait cycle was defined as AP-MoSmean . The fast/preferred ratio of AP-MoSmean /ML-MoSPOS (AP-MoSmean (Fast/Preferred)/ML-MoSPOS (Fast/Preferred)) and the fast-preferred difference of ML-MoSNEG (ML-MoSNEG (Fast-Preferred)) were compared between groups. ML/AP-MoS at the preferred/fast gait was also compared between 12 gait events and groups. The Japanese version of the Mini-Balance Evaluation Systems Test (J-Mini-BESTest), the Japanese version of the Activities-specific Balance Confidence Scale (J-ABC scale), and the number of falls in the past year were obtained from all subjects. ML-MoSPOS (Fast/Preferred), ML-MoSNEG (Fast-Preferred), and AP-MoSmean (Fast/Preferred) were significantly correlated with J-Mini-BESTest. Gait balance evaluation based on MoS may reflect an individual's balance function. In fast gait, ML-MoS at foot flat and toe off and AP-MoS at just before heel strike were highly likely to be gait events to identify elderly adults with balance disorders.